Policies to scale up climate smart investment in Indo-Gangetic Plain in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
A research project has been undertaken in collaboration with the World Bank to influence the agricultural policy of the states Punjab and Rajasthan to scale up climate smart agriculture